Brand Activation Klub Merby “Happy-Happy Holiday Merby One Day Course” - Imam Saifudin (Interaksi, 2012)
Being the oldest creativity and arts institutions in Semarang, gives Klub Merby a lot of experience and achievement. However, when it brand is no longer exists and rarely known to the public, it become attention to be solved. This project is designed to increase brand awareness from Klub Merby as educational institutions that focus on art and creativity as well as being a credible institution in developing talents of children. Brand activation strategies into marketing communications activities Klub Merby would be effective in increasing brand awareness and interest in Klub Merby through approachment from AIDDA, IMC, and promotion mix. By taking a moment of school holiday time, the theme of the event is the “Creative Holiday with Klub Merby” by titled “Happy-Happy Holiday Merby One Day Course”. event aims to fill children's holiday with creative and interesting games with their parents and to make bonding between parents and their children with Klub Merby. This event was also filled by singing contest, drawing contest and completing picture, as well as a fashion show competition to hone talents and self-esteem for the children. Through this event, target audience is expected to know better about Klub Merby and impact of increasing the number Klub Merby’s students in the end. Based on post event research, awareness from target audience of Klub Merby increase from the original 32,5% to 72,5%. While the interest of target audience to put their children to Klub Merby increased 13% from the original 35,3% to 46,7%. It means, brand activation is effective to increase awareness and interest of audience. This project is expected to provide the implications from academic and practical aspects. Implications of the academic work of art in the form of contributions to enrich the knowledge of the application of IMC, AIDDA and brand activation. Meanwhile, the practical implications of providing knowledge and experience to create effective promotional activities and fit for purpose.